Integrated transcriptomics and metabolomics analyses provide new insights into cassava in response to nitrogen deficiency - Wang, Yu; Chu, Jing; Zhang, Haoyang; Ju, Hao; Xie, Qing; Jiang, Xingyu (Frontiers in Plant Science, 2025)
Nitrogen deficiency is a key constraint on crop yield. Cassava, the world’s sixth-largest food crop and a crucial source of feed and industrial materials, can thrive in marginal soils, yet its yield is still significantly affected by limited nitrogen availability. Investigating cassava’s response mechanisms to nitrogen scarcity is therefore essential for advancing molecular breeding and identifying nitrogen-efficient varieties. This research undertook a comprehensive analysis of cassava seedlings’ physiological, gene expression, and metabolite responses under low nitrogen stress. Findings revealed that nitrogen deficiency drastically suppressed seedling growth, significantly reduced nitrate and ammonium transport to aerial parts, and led to a marked increase in carbohydrate, reactive oxygen species, and ammonium ion levels in the leaves. Transcriptomic and metabolomic analyses further demonstrated notable alterations in genes and metabolites linked to carbon and nitrogen metabolism, flavonoid biosynthesis, and the purine metabolic pathway. Additionally, several transcription factors associated with cassava flavonoid biosynthesis under nitrogen-deficient conditions were identified. Overall, this study offers fresh insights and valuable genetic resources for unraveling cassava’s adaptive mechanisms to nitrogen deprivation.